Tumor Progression and Metastasis - Lasfar, Ahmed; Cohen-Solal, Karine (Physiology, 2020)
This book offers significant coverage on different aspects of cancer from risk factors to the mechanisms leading to tumor progression and metastasis. Although tremendous progress has been made in cancer research and treatment, cancer metastasis remains a major unmet clinical need. The life and death of many cancer patients hangs on the degree of metastasis. This book provides new perspectives for diagnosis and cancer therapy. It includes new technologies and a new basis for current cancer therapies. To guarantee the high quality of this book, important topics are included and rigorously discussed in a simple and authentic way. The book addresses important challenges governing tumor progression and metastasis and brings new responses to both diagnosis and therapy. This book is a great source of knowledge and will be useful for researchers, medical doctors, oncologists, graduate and medical students, continued medical educators, health care providers, and all individuals interested in understanding cancer and its challenges.